ANALISIS MEDIA PUZZLE TERHADAP PENGUASAAN KOSA KATA KELAS I DENGAN MENGGUNAKAN MODEL JIGSAW - Anggraini, Rhohimah R.; Murniviyanti, Liza; Pratama, Aldora (UNIB Press, 2022)
The purpose of this study is to find out, describe and analyse the use of a media puzzle game in Jigsaw Model of vocabulary mastery for class one of elementary school students. This research uses Descriptive Qualitative Method. The population of this research is Class 1 of Elementary School 19 Air Salek which consists of 23 students. Methods of data collection using observations, interviews and documentation. Based on the research proves that the media puzzle game in jigsaw model is worthy of use. It is concluded that the use of media and model rises 18 vocabularies on each students at the average. The previous results are 20 of 52 vocabularies on given semester. Therefore, the use of media puzzle game in jigsaw model is one of the best way to increase the students’ vocabularies.